The effect of Ferbanat L nano-fertilizer on the growing of Petunia x grandiflora ’Musica Blue’ - Kisvarga, Sz.; Kerezsi, R.; Kohut, I.; Tillyné Mándy, A. (International Journal of Horticultural Science, 2014)
During our experiment, the effect of Ferbanat L concentrations were examined by Petunia x grandiflora ‘Musica Blue’ production. The leaf and shoot length, number of flower buds, diameter of flowers, and the date of appearing the first buds were measured. The solution of Ferbanat L in 0.1 % concentration was the most effective on shoot length (21.7 cm). Remarkable increase was observed by the other treatment groups as well comparing to the control group (5.6 cm), the plants treated with solution of Ferbanat L 0.2% (16.5 cm) and 0.3% (14.4 cm) had significant effect as well. The nano-fertilizer had not positive effect on the other examined parameters as leaf and flower size, number of flower buds or chlorophyll content. The culture period shortened five days.